Optimal design of a Stewart platform using the global transmission index under determinate constraint of workspace. (October 2017) - Xie, Zenghui; Li, Ge; Liu, Gangfeng; Zhao, Jie
The Stewart platform is a typical parallel manipulator. It is used as a space docking mechanism whose requirement for movement scope is determinate. This article addresses the dimension synthesis of the space docking mechanism. First, this article compares the common indexes used to evaluate the performance of parallel manipulator. These indexes can mainly be divided into two types. The evaluation indexes based on the Jacobian matrix, including the singular value index, the manipulability index, and condition index, are derived from the Jacobian matrix of the manipulator, and the transmissibility indexes, such as pressure angle, transmission angle, and motion/force transmission index, lay emphasis on the power transmission ability of manipulator. This article proposes the global transmission index under determinate constraint of workspace on the basis of the previous transmissibility indexes to evaluate the performance of parallel manipulator whose workspace is determinate and movement is the combination of translation and rotation. And the optimization design of the manipulator is carried out by taking the global transmission index under determinate constraint of workspace into account. The detailed process of determining the optimal configuration for the Stewart manipulator used as space docking mechanism is presented. The optimal result is gotten, which has a large value of global transmission index under determinate constraint of workspace in the required workspace, and a simulation is carried out to verify the validity of the optimal result.